Integrasi Perbankan Syariah Dalam Mendorong Pembangunan Berkelanjutan: Tantangan dan Prospek Masa Depan - Ayu Alifia, Putri Ismukhanah (OECONOMICUS Journal of Economics, 2023)
Sustainable development is an issue that is often discussed these days in various disciplines, including economic development. The existence of sustainable development aims to meet the needs of today's society without having to sacrifice the rights of the next generation to sustainability and the natural environment. The concept of sustainable development includes three main pillars, namely the economic pillar, social pillar and environmental pillar in its implementation. In this journal research using qualitative methods to find out the integration of Islamic banking with sustainable development which is very important because an environmentally friendly economy can be an innovation that drives the growth of Islamic banking. Starting from the existence of financing for environmentally sound business activities, which is around 24.70% of total financing, namely at 41.91 trillion rupiah in 2022 from the economic aspect, based on the annual report issued by Bank Syariah Indonesia. Islamic banking as a forum to encourage the development of sustainable development must always innovate to welcome an environmentally friendly life and optimize it to welcome future prospects.